Inégalités dans l’accès et dans le financement des soins au Tadjikistan : le rôle des stratégies informelles et des migrations - Sandra Pellet (Revue de la Régulation)
Informal payments to healthcare professionals in post-soviet health systems persisted, despite the healthcare reforms. That is true in independent Tajikistan, where the increase in those payments has been associated with increased forgone care and the deterioration of trust towards health professionals which has been. What is the role played by the different informal payment practices? Are they a source of mistrust or a means of restoring trust? Are informal payments adjusted to patients’ income or a source of inequality? Contrary to popular belief, informal payments do not make the system progressive. The poorest are more likely to forgo care. Different strategies are then put in place by households: informal solidarity, reliance on traditional medicine, mobilization of social capital. What if migration was part of these strategies to improve their access to healthcare?